Serum oxidized low-density lipoprotein level as a marker of oxidative stress in patients undergoing hyperbaric oxygen therapy - Kudret Keskin; Hakan Kilci; Gökhan Aksan; Gökhan Çetinkal; Süleyman Sezai Yıldız; Füsun Kocaman Türk; Gülsüm Bingöl (KARE Publishing, 2017)
Objective: Oxidative stress (OS) is involved in the pathogenesis of atherosclerosis. Hyperbaric oxygen therapy (HBOT), in which 100% oxygen is inhaled under hyperbaric pressure, may create OS. Therefore, the aim of this research was to measure the serum oxidized low-density lipoprotein (oxLDL) level in patients undergoing HBOT. Methods: Twenty-nine patients who underwent HBOT to treat various diseases were enrolled in this study. The serum oxLDL level was measured at the beginning of the first and after the 10th therapy session. Results: There was no significant difference between the oxLDL level of patients before and after HBOT (4.96+-0.1 vs. 4.94+-0.1 U/mL; p=0.36). Conclusion: HBOT seems to be safe in terms of oxLDL production up to 10 sessions. However, further large-scale studies investigating longer duration of HBOT treatment are required to understand the role of OS.